2005
DOI: 10.1007/s00125-005-1804-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in rat pregnancy alters renal calcium and magnesium reabsorption and bone formation in adult offspring

Abstract: Aims/hypothesis: We tested the hypothesis that diabetes in pregnancy can result in the in-utero reprogramming of renal calcium and magnesium handling and of bone formation in the offspring, which persists into adulthood. Methods: Male offspring of streptozotocintreated diabetic rats (OD rats) and of control non-diabetic animals (OC rats) were investigated as neonates and at 8, 12 and 16 weeks of age. Results: Compared with OC rats, urinary calcium and magnesium output was significantly reduced in OD rats at ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…2B). The monoclonal anti-PMCA antibody detected a broad protein band at ϳ140 kDa (ϳ133 to 147 kDa), as well as a smaller band at 92 kDa, consistent with previous observations (7). These bands were absent from negative control blots (data not shown).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2B). The monoclonal anti-PMCA antibody detected a broad protein band at ϳ140 kDa (ϳ133 to 147 kDa), as well as a smaller band at 92 kDa, consistent with previous observations (7). These bands were absent from negative control blots (data not shown).…”
Section: Resultssupporting
confidence: 91%
“…Kidneys were harvested from a separate group of control (n ϭ 5 from 5 litters) and LP (n ϭ 5 from 5 litters) rats. Tissue was homogenized, and renal calcium transporter expression was determined according to the method of Bond et al (7). The antisera used were mouse monoclonal anti-calbindin-D28K (1:2,500 dilution; Sigma), mouse monoclonal anti-PMCA 5F10 (1:1,500 dilution; Cambridge Bioscience, Cambridge, UK), affinity-purified rabbit polyclonal anti-ECaC1 (1:1,000 dilution; Alpha Diagnostic International, San Antonio, TX), and polyclonal rabbit anti-NHE3 [Na ϩ /H ϩ exchanger 3 (NHE3), 1:300 dilution; Alpha Diagnostic International].…”
Section: Methodsmentioning
confidence: 99%
“…This distribution of bone mass further away from the central axis of the bone in CDM resulted in higher axial moment of inertia, which is likely to increase the bending bone strength 3738. In contrast to these findings, Bond et al 3 found that in comparison to controls, adult offspring of streptozotocin-induced diabetic rats had thicker long bone (femoral and tibial) cortical shells, arising from deposition of bone on the endosteal surface but not the periosteal surface. At the distal ends of long bones, these animals had reduced trabecular volume compared with the adult offspring of nondiabetic rats 3.…”
Section: Discussionmentioning
confidence: 95%
“…Abnormalities of skeletal mineralisation have also been reported in infants born to mothers with type 1 diabetes mellitus and in offspring of streptozotocininduced diabetic rats 3. Mimouni et al 4 reported a 10% reduction in the radial bone mineral content (BMC), measured by single photon absorptiometry, in infants born to mothers with type 1 diabetes mellitus compared with controls.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation